MORPHO-CHEMICAL DIVERSITY AND RAPD FINGERPRINTING IN WHITE FLESH GUAVA CULTIVARS - M. Usman1; Q. Zaman; B. Fatima; I. A. Rana; F. S. Awan (Journal of Animal and Plant Sciences, 2020)
Different elite strains of Guava cultivars ‘Round’ and ‘Pyriform’ collected from a single locality were evaluated for phenotypic, physico-chemical and genetic variation. Phenotypic variability was observed in strains of ‘Round’ and ‘Pyriform’ cultivars in leaf and fruit physical traits. In ‘Round’ strains, variation in leaf shape and other traits were less compared to ‘Pyriform’ strains. Strains Gola No. 1 ‘G1’, Surahi ‘S’ and Large Surahi ‘LS’, had less seeds compared with other strains. Among ‘Round’ strain ‘G1’ and ‘Pyriform’ strain ‘LS’ were better for most of the physical traits. In chemical traits, TSS:TA and total sugars showed variation among strains and ‘Round’ strain Small Gola ‘SG’ and ‘Pyriform’ strain ‘S’ were better for TSS:TA and TS. Overall, non-reducing sugars were higher in ‘Round’ while other fruit physico-chemical traits were similar in both varieties. Five out of fifteen randomly amplified polymorphic DNA (RAPD) primers produced 37 bands. Molecular variance was higher (74%) among strains compared with varieties (26%). Different strains of ‘Round’ and ‘Pyriform’ shaped cultivars were clustered as two distinct groups in the dendrogram generated by UPGMA method. The primers K1, K4 and K7 were highly polymorphic for selected guava genotypes. This base line study could be helpful in germplasm characterization, varietal identification and development of sequence characterized amplified regions (SCAR) marker associated to different traits.
Keywords: Fruit size; fruit quality; Gola; Surahi; DNA marker